In Vitro Gastrointestinal Digestion Impact on the Bioaccessibility and Antioxidant Capacity of Bioactive Compounds from Tomato Flours Obtained after Conventional and Ohmic Heating Extraction - Marta C. Coelho; Tânia B. Ribeiro; Carla Oliveira; Patricia Batista; Pedro Castro; Ana Rita Monforte; António Sebastião Rodrigues; José Teixeira; Manuela Pintado (Foods, 2021)
In times of pandemic and when sustainability is in vogue, the use of byproducts, such as fiber-rich tomato byproducts, can be an asset. There are still no studies on the impact of extraction methodologies and the gastrointestinal tract action on bioactive properties. Thus, this study used a solid fraction obtained after the conventional method (SFCONV) and a solid fraction after the ohmic method (SFOH) to analyze the effect of the gastrointestinal tract on bioactive compounds (BC) and bioactivities. Results showed that the SFOH presents higher total fiber than SFCONV samples, 62.47 ± 1.24–59.06 ± 0.67 g/100 g DW, respectively. Both flours present high amounts of resistant protein, representing between 11 and 16% of insoluble dietary fiber. Furthermore, concerning the total and bound phenolic compounds, the related antioxidant activity measured by 2,2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) radical cation decolorization assay presented significantly higher values for SFCONV than SFOH samples (p < 0.05). The main phenolic compounds identified in the two flours were gallic acid, rutin, and p-coumaric acid, and carotenoids were lycopene, phytofluene, and lutein, all known as health promoters. Despite the higher initial values of SFCONV polyphenols and carotenoids, these BCs’ OH flours were more bioaccessible and presented more antioxidant capacity than SFCONV flours, throughout the simulated gastrointestinal tract. These results confirm the potential of ohmic heating to modify the bioaccessibility of tomato BC, enhancing their concentrations and improving their antioxidant capacity.